Fetal macrosomia in home and birth center births in the United States: Maternal, fetal, and newborn outcomes. Issue 4 (15th October 2020) - Pillai, Sabrina; Cheyney, Melissa; Everson, Courtney L.; Bovbjerg, Marit L.
Abstract: Background: Fetal macrosomia is associated with negative outcomes, although less is known about how severities of macrosomia influence these outcomes. Planned community births in the United States have higher rates of gestational age‐adjusted macrosomia than planned hospital births, providing a novel population to examine macrosomia morbidity. Methods: Maternal and neonatal outcomes associated with grade 1 (4000‐4499 g), grade 2 (4500‐4999 g), and grade 3 (≥5000 g) macrosomia were compared to normal birthweight newborns (2500‐3999 g), using data from the MANA Statistics Project—a registry of planned community births, 2012‐2018 ( n = 68 966). Outcomes included perineal trauma, postpartum hemorrhage, cesarean birth, neonatal birth injury, shoulder dystocia, neonatal respiratory distress, neonatal intensive care unit (NICU) stay >24 hours, and perinatal death. Logistic regressions controlled for parity and mode of birth, obesity, gestational diabetes, and preeclampsia. Results: Sixteen percent of the sample were grade 1 macrosomic, 3.3% were grade 2 macrosomic, and 0.4% were grade 3 macrosomic. Macrosomia grades 1‐3 were associated in a dose‐response fashion with higher odds of all outcomes, compared to non‐macrosomia. The adjusted odds ratios and 95% confidence intervals for postpartum hemorrhage for grade 1, grade 2, and grade 3 macrosomia vs normal birthweight were 1.75 (1.56‐1.96), 2.12 (1.70‐2.63), and 5.18 (3.47‐7.74), respectively. Other outcomes had similar patterns. Discussion: The adjusted odds of negative outcomes increase as grade of macrosomia increases in planned community births; results are comparable with the published literature. Pre‐birth fetal weight estimation is imprecise; prenatal supports and shared decision‐making processes should reflect these complexities.